WORK SAFETY PROTECTION SYSTEM BASED ON ARDUINO UNO - Hermansyah Hermansyah; Muhammad Aqdar Fitrah (Jurnal Media Elektrik, 2024)
This research aims to develop an effective and reliable work safety protection system based on Arduino Uno. The system is designed to detect hazards in the workplace, such as suspicious movements that may cause accidents for industrial workers. Arduino Uno is used as the brain of the system, and sensors connected to the microcontroller serve as input devices that detect actions not in accordance with safety procedures. When the sensors detect a hazard, Arduino Uno will activate an alarm and automatically take the necessary control actions. This research involves programming the Arduino Uno, selecting the appropriate sensors, hardware integration, and thorough system testing. The developed system is expected to enhance workplace safety and provide better protection for workers. System testing is conducted using a simulated work environment that depicts different hazard scenarios. The test results show that the Arduino Uno-based work safety protection system functions as expected. The installed sensors accurately detect hazards such as excessive temperature, fire, toxic gases, excessive vibrations, and unwanted movements in the work area. Arduino Uno receives signals from these sensors and quickly responds by activating alarms and taking appropriate protective actions. Interpretation of the test results indicates that the developed system can effectively help identify potential hazards and provide the necessary protection for workers in the manufacturing industry